Metaproteomic Discovery and Characterization of a Novel Lipolytic Enzyme From an Indian Hot Spring - Sander, Dennis; Yu, Yanfei; Sukul, Premankur; Schäkermann, Sina; Bandow, Julia E.; Mukherjee, Trinetra; Mukhopadhyay, Subhra Kanti; Leichert, Lars I. (Frontiers in Microbiology, 2021)
Lipolytic enzymes are produced by animals, plants and microorganisms. With their chemo-, regio- and enantio-specific characteristics, lipolytic enzymes are important biocatalysts useful in several industrial applications. They are widely used in the processing of fats and oils, detergents, food processing, paper and cosmetics production. In this work, we used a new functional metaproteomics approach to screen sediment samples of the Indian Bakreshwar hot spring for novel thermo- and solvent-stable lipolytic enzymes. We were able to identify an enzyme showing favorable characteristics. DS-007 showed high hydrolytic activity with substrates with shorter chain length (< C8) with the maximum activity observed against p-nitrophenyl butyrate (C4). For substrates with a chain length > C10, significantly less hydrolytic activity was observed. A preference for short chain acyl groups is characteristic for esterases, suggesting that DS-007 is an esterase. Consistent with the high temperature at its site of isolation, DS-007 showed a temperature optimum at 55 °C and retained 80 % activity even after prolonged exposure to temperatures as high as 60 °C. The enzyme showed more than 50 % of its optimum activity in a pH-range between pH 8.0 and pH 9.5, with its optimum at pH 9.5. DS-007 also exhibited tolerance towards organic solvents at a concentration of 1 % (v/v). 1 % of methanol increased the activity of DS-007 by 40 % in comparison to the optimum conditions without solvent. In the presence of 10 % methanol, DMSO or isopropanol DS-007 still showed around 50 % activity. This data indicates that DS-007 is a temperature- and solvent-stable thermophilic enzyme with reasonable activity even at lower temperatures as well as a catalyst that can be used at a broad range of pH with an optimum in the alkaliphilic range, showing the adaption to the habitat’s temperature and alkaline pH.